PI-RADS 2.1 – Image Interpretation: The Most Important Updates and Their Clinical Implications - Beyer, Thomas; Schlemmer, Heinz-Peter; Weber, Marc-André; Thierfelder, Kolja M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background Multiparametric magnetic resonance imaging (MRI) of the prostate plays a central role in the diagnosis of patients with suspected prostate cancer. The increasing distribution and application of the guideline for the standardization of image acquisition, evaluation, and reporting (Prostate Imaging – Reporting and Data System, PI-RADS), which was updated in 2019 to version 2.1, contributes to the success of the technique.Materials and Methods The most important updates of PI-RADS version 2.1 presented in 2019 compared to the previous version PI-RADS 2.0 are highlighted and interpreted with regard to their clinical implications.Results PI-RADS version 2.1 aims to simplify the application of the scoring scheme without changing the basic concept of dominant sequences (DWI in the peripheral zone, T2 in the transition zone). Of particular importance are the increasing role of diffusion-weighted imaging in the transition zone, the now mandatory high b-value of at least 1400 s/mm2, and new information on the assessment of the central zone and the anterior fibromuscular stroma.Conclusion PI-RADS version 2.1 published in 2019 addresses a number of changes to the previous version, including both the examination technique and image interpretation. Prospective clinical studies have yet to prove the extent to which the goals of reducing interreader variability and increasing the detection rate in the transition zone will be achieved.Key Points: Citation FormatHintergrund Die multiparametrische Magnetresonanztomografie (MRT) der Prostata übernimmt inzwischen eine zentrale Rolle in der Diagnostik bei Patienten mit Verdacht auf Prostatakarzinom. Zum Erfolg der Methode trägt die zunehmende Verbreitung der zuletzt im Jahr 2019 auf die Version 2.1 aktualisierte Leitlinie zur Standardisierung von Bildakquisition, Auswertung und Befundung (Prostate Imaging – Reporting and Data System, PI-RADS) bei.Material und Methoden Die zentralen Neuerungen der im Frühjahr 2019 vorgestellten PI-RADS-Version 2.1 gegenüber der Vorgängerversion PI-RADS 2.0 werden vorgestellt und bezüglich ihrer klinischen Implikationen diskutiert.Ergebnisse Die PI-RADS-Version 2.1 zielt darauf ab, die Anwendung zu vereinfachen, ohne dabei das Grundkonzept der dominanten Sequenz (DWI in der peripheren Zone, T2 in der Transitionszone) zu ändern. Von besonderer Bedeutung sind die stärkere Gewichtung der Diffusionsbildgebung in der Transitionszone, der nun obligatorische hohe b-Wert von mindestens 1400 s/mm2 und neue Hinweise zur Beurteilung der zentralen Zone und des anterioren fibromuskulären Stromas.Schlussfolgerung Die 2019 veröffentlichte PI-RADS-Version 2.1 adressiert verschiedene Änderungen, die sowohl Untersuchungstechnik als auch Befundung betreffen. Inwieweit sich damit die Ziele der Reduktion der Interreader-Variabilität und der Erhöhung der Detektionsrate in der Transitionszone erreichen lassen, müssen prospektive klinische Studien zeigen.Kernaussagen: Zitierweise
Keywords: prostate; PI-RADS; prostate cancer; uroradiology; MR imaging